Sleep duration, sleep quality, and obesity risk among older adults from six middle‐income countries: Findings from the study on global ageing and adult health (SAGE). Issue 6 (18th August 2014) - Gildner, Theresa E.; Liebert, Melissa A.; Kowal, Paul; Chatterji, Somnath; Josh Snodgrass, J.
<x xml:space="preserve">Abstract</x> Objectives Changes in sleep patterns often occur in older adults. Previous studies have documented associations between sleep duration, sleep quality, and obesity risk in older individuals, yet few studies have examined these trends in lower‐income countries. The present cross‐sectional study uses nationally representative datasets from six countries to examine these relationships. Methods Two hypotheses related to obesity risk and sleep patterns were tested using data from the first wave of the World Health Organization's Study on global AGEing and adult health (SAGE). This longitudinal study draws on samples of older adults (>50 years old) in six middle‐income countries (China, Ghana, India, Mexico, Russian Federation, and South Africa). Self‐report data were used to measure sleep duration, sleep quality, lifestyle and sociodemographic information, while anthropometric measurements were collected to assess body mass index (BMI) and waist circumference (WC). Multiple linear regressions were used to examine the relationship between sleep patterns and obesity risk while controlling for lifestyle factors. Results Shorter sleep durations in both men and women were significantly associated with higher BMI and WC measures (P < 0.05). Low sleep quality did not significantly contribute to increased obesity risk. Surprisingly, high sleep quality was significantly associated with increased male BMI and WC in China and India (P < 0.01). Conclusions This study documented an association between short sleep duration and increased obesity risk, which is important given the global increase of obesity‐related diseases. Am. J. Hum. Biol. 26:803–812, 2014. © 2014 Wiley Periodicals, Inc.